The Role of the Audit Committee in SPI Risk-Based Audit Supervision and Its Implications for the Quality of Financial Reporting - Rimba Simandjuntak; Renny Maisyarah (Journal of Research in Social Science and Humanities, 2026)
This study examines the effect of the Audit Committee on Financial Reporting Quality through the implementation of Risk-Based Internal Audit conducted by the Internal Audit Unit (SPI) as a mediating variable at PT Pelabuhan Indonesia I (Pelindo I) Medan. The research adopts a quantitative approach with an explanatory design. Primary data were collected using a Likert-scale questionnaire administered to 45 respondents (census sampling) comprising SPI personnel, audit committee members, and accounting and finance staff. Data were analyzed using SEM-PLS (SmartPLS) with a bootstrapping procedure to test direct and indirect effects. The results indicate that the Audit Committee has a positive and significant effect on the implementation of SPI risk-based audit oversight, and that SPI risk-based audit oversight has a positive and significant effect on financial reporting quality. The mediation test also confirms a positive and significant indirect effect of the Audit Committee on financial reporting quality through SPI risk-based audit oversight. These findings suggest that improvements in financial reporting quality are driven not only by the Audit Committee's direct effectiveness, but more importantly by strengthening the implementation of risk-based internal audit oversight. Practically, firms should enhance the Audit Committee's role in promoting risk-based audit planning, execution, reporting, and follow-up processes to ensure financial reporting becomes more reliable and timely.